Integrating Educational Theories for Effective Learning: A Comprehensive Analysis of Behaviorism, Nativism, Cognitivism, Functionalism, Constructivism, Humanism, and Cybernetics in Education - Chusnul Chatimah Azis; Dede Irman Pirdaus; Rini Cahyandari (Communication In Research And Publications, 2024)
Education is an important part of human development. Various educational theories have emerged over time, each with its unique approach to the learning process. In this abstract, we summarize several major educational theories including behaviorism, nativism, cognitivism, functionalism, constructivism, humanism, and cybernetics. Each theory has a different view of how humans learn and how teachers can facilitate learning. We also note some of the advantages of each theory and how they have influenced educational practice. Combining these approaches can help achieve effective and sustainable learning.